2023
DOI: 10.1039/d2ee04137e
|View full text |Cite
|
Sign up to set email alerts
|

Translucent perovskite photovoltaics for building integration

Abstract: Transparent photovoltaics provide diverse levels of average visible transmittance (AVT) along concurrent light harvesting, making glass façades and windows accessible for photovoltaics. However, improvements in power conversion efficiency (PCE) and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
(93 reference statements)
0
11
0
Order By: Relevance
“…[3] Among solar cells, no absolute records regarding light utilization efficiency (LUE) and no significant novel absorber materials for single-junction devices have been reported during the last year; most of the reports on transparent cells focus on the optimization of the absorber layer thickness and on transparent electrodes of otherwise top-performing opaque devices. Notably, Ritzer et al [46] reported the first micro-patterned translucent twoterminal all-perovskite tandem solar cells with PCEs as high as 15.0% at average visible transmittance (AVT) of 12% and 9.3% at 31% AVT, for LUE values of 1.8% and 2.9%, respectively. Nevertheless, the latest transparent OPV continues to outperform most transparent PSCs in terms of LUE.…”
Section: Transparent and Semitransparent Photovoltaic Cellsmentioning
confidence: 99%
“…[3] Among solar cells, no absolute records regarding light utilization efficiency (LUE) and no significant novel absorber materials for single-junction devices have been reported during the last year; most of the reports on transparent cells focus on the optimization of the absorber layer thickness and on transparent electrodes of otherwise top-performing opaque devices. Notably, Ritzer et al [46] reported the first micro-patterned translucent twoterminal all-perovskite tandem solar cells with PCEs as high as 15.0% at average visible transmittance (AVT) of 12% and 9.3% at 31% AVT, for LUE values of 1.8% and 2.9%, respectively. Nevertheless, the latest transparent OPV continues to outperform most transparent PSCs in terms of LUE.…”
Section: Transparent and Semitransparent Photovoltaic Cellsmentioning
confidence: 99%
“…4 Moreover, their production can be carried out using low-cost and scalable processes, such as solution-based techniques, making them a viable option for widespread adoption in the photovoltaic industry. Their versatility extends to various applications, from building-integrated photovoltaics 5 to flexible solar panels, 6 making them a promising choice for various contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990's, the efforts to develop alternative photovoltaic (PV) technologies to silicon have been steadily increasing. 1,2 The emergence of solar cells integrating fully organic or hybrid materials in the photoactive layer, 3,4 and more recently the development of semi-transparent devices 5,6 have opened up new prospects for PV applications in IoT 7,8 (Internet of Things) devices, buildings, 9–12 vehicles 13 and greenhouses. 14,15 Among these technologies, Dye-Sensitized Solar cells (DSSCs) are attractive because they combine many advantages.…”
Section: Introductionmentioning
confidence: 99%